ANALISIS PENGELOLAAN TERTIB ADMINISTRASI PEMERINTAHAN DESA AROMANTAI KECAMATAN PULAUBERINGIN KABUPATEN OGAN KOMERING ULU SELATAN - Tri Sukmawati; Marratu Fahri; Eva Susanti; Aprilia Lestari (PT. Hasba Edukasi Mandiri, 2026)
Village administration is the foundation for effective, transparent, and accountable public services. However, in Aromantai Village, administrative management remains suboptimal, characterized by irregular record-keeping, limited infrastructure, and low human resource capacity among village officials. This situation impacts the suboptimal service delivery to the community, necessitating an analysis of village administration management to improve the quality of public services. This research was conducted from February to March 2026 using qualitative research methods and a descriptive approach. Data collection techniques included observation, documentation, and interviews with informants including the Village Head, Treasurer, Secretary, Head of General Affairs, and community leaders. The focus of this research included the completeness of administrative books, data accountability, effectiveness and efficiency, and document order. The results indicate that village administration in Aromantai Village has generally been running quite well. Most administrative books are complete, but they are not yet fully completed consistently. Data accountability is quite good, but there is still room for improvement in recording accuracy. Administrative effectiveness and efficiency are not optimal due to limited facilities and a manual system. Documentation order has been maintained through classification, labeling, and segregation of archives, but challenges remain in consistent recording and retrieval of old documents. Therefore, improvements in staff discipline, provision of facilities and infrastructure, and development of a digital system are needed to support more effective, efficient, and accountable administration.